Pendidikan Dan Stratifikasi Sosial: Kebijakan dan Praktek Pendidikan Dalam Mengurangi Stratifikasi Sosial di Lembaga Pendidikan - Aulia Sari, Febby; Yasin, Muhammad (Yayasan Miftahul Ulum Sangatta Kutai Timur (KEP. MENKUMHAM RI No. AHU-0014779.AH.01.04.Tahun 2018) bekerjasama dengan Jurusan Tarbiyah STAI SANGATTA Kab. Kutai Timur., 2024)
Education is an important and complex social phenomenon, influenced by various social, economic and cultural factors. The relationship between education and social stratification is interrelated in shaping the structure of society, especially in studying how education affects opportunity and equality, as well as how social stratification impacts individual success in various levels of society. Education aims to encourage the progress of humanity and the nation. This research aims to explain educational policies and practices that can reduce social stratification and identify the obstacles that influence these efforts. The study was conducted at SMKN 1 Sangatta Utara using qualitative methods through direct interviews and observation. The research results show that despite challenges and obstacles in the education sector, such as unequal access and economic disparities, SMKN 1 Sangatta Utara strives to reduce inequality by implementing inclusive and fair education policies. The school's efforts have had a positive impact in creating more equitable access to education and reducing social stratification.